EVIDENCE-BASED PRACTICE TEACHING INTEGRATION IN COLLEGE NURSING STUDIES: HISTORICAL AND LEGAL ASPECTS - Šakalytė, Danguolė; Indrašienė, Valdonė (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
To better understand and analyze the education of evidence-based practice, it is necessary to review the context and premises of the formation of evidence-based practice itself. The beginning of the evidence-based practice movement in the teaching of health professionals’ dates back to 1910 and looking at the health care system; first, there was evidence-based medicine. In 1990, Sackett's initiative at McMaster University in Canada, it was decided to change the term "evidence-based medicine" to "evidence-based practice" (Mackey & Bassendowski, 2017; Thom & Eaves, 2015). In nursing, the beginning of evidence-based practice is linked to the reforms of nursing science and practice by the first nursing researcher, Florence Nightingale, from 1854 to 1910, although the term of “evidence-based practice” was not yet known at the time. The professional training of nurses as one of the leading health professionals is related to health policy and the development of nursing science. The European Qualifications Framework (EHEA) defines the expected learning outcomes for professionals with a bachelor's degree, including the skills to find, evaluate, reflect, and apply scientific information in practice (Bologna Working Group, 2005). Despite international and national recommendations, it is difficult for many higher education institutions to refine the steps of teaching evidence-based practice in nursing study programs. These difficulties are revealed by the ambiguity in the definition of the concept of evidence-based practice (Horntvedt et al. 2018).The problematic question is: What is the basis for integrating evidence-based practice training into college nursing study programs?The study is based on the scientific literature review.